Expression levels of genes involved in lipogenesis and cholesterol synthesis in adenomyosis - Yalaza Cem; Antmen Şerife Efsun; Canacankatan Necmiye; Tuncel Ferah; Aytan Hakan; Erden Ertürk Sema (Türk Biyokimya Dergisi, 2024)
Adenomyosis is a benign uterine disease that occurs with the invasion of the endometrial gland and stoma into the myometrium. The etiology and molecular pathology of adenomyosis are not yet fully understood. Tissue samples of patients diagnosed with adenomyosis and healthy endometrial tissues were investigated for the lipogenesis and cholesterol synthesis pathways. It was aimed to determine the difference between adenomyosis and healthy endometrial tissues in terms of lipid metabolism and to investigate the mechanism of adenomyosis in this context.